The Effect of Independent Commissioner’s Moderation of CSR and Institutional Ownership on Tax Avoidance - Baiq Fitri Arianti (Universitas Negeri Malang, 2020)
This research aims at providing empirical evidence of the effects of corporate social responsibility (CSR) and institutional ownership on tax avoidance with independent commissioner as the moderator. The study’s population is 66 mining and agricultural companies listed in the Indonesia Stock Exchange from 2013 - 2017. Employing a purposive sampling technique, 10 mining and agricultural companies are taken as the samples out of 50 annual reports from 2013 - 2017 observed. The research employs the Moderated Regression Analysis (MRA) as the data analysis technique. The research results indicate that corporate social responsibility (CSR) variable does not influence tax avoidance and institutional ownership variable influences tax avoidance. Independent commissioner may weaken the effect of corporate social responsibility (CSR) on tax avoidance and strengthen the effect of institutional ownership on tax avoidance. The implication of this research is to examine the importance of tax payment and expectedly increase the community’s awareness, especially related parties, of the obligation to pay their taxes appropriately and, with the research’s results, the public is expected to be aware of the importance of paying taxes, especially large companies, so as not to take tax avoidance measures for Indonesia’s improved and stable economy.